Study on the current status of self-perceived burden and its correlation with caregiver reactions in spinal cord injury patients under the background of medical consortium - Jie Jiang; Jingjun Xie; Jianwei Sun; Qi Sun (Frontiers in Psychology)
ObjectiveThe current study tried to investigate the self-perceived burden (SPB) status and its influencing factors in spinal cord injury (SCI) patients under the background of medical consortium, and to analyze the relationship between SPB and caregiver reactions.MethodsA total of 120 SCI patients treated within the Huzhou medical consortium were selected as study subjects using a convenience sampling method. Data were collected using a general information questionnaire, the SPB Scale, and the Caregiver Reaction Assessment (CRA). Multiple linear regression analysis was used to identify the influencing factors of SPB, and Spearman correlation analysis was used to examine the relationship between SPB and caregiver reactions.ResultsThe mean SPB score for SCI patients within the medical consortium was (31.06 ± 9.10). Multiple linear regression analysis revealed that patients’ ability to perform activities of daily living, SCI-related complications, per capita monthly household income, and marital status were independent factors influencing SPB (p < 0.05). SPB was positively correlated with the health problems, economic problems, time disruption, and lack of family support dimensions of the caregiver reaction assessment, while it was negatively correlated with the self-esteem dimension (p < 0.001).ConclusionThe SPB of SCI patients is at a moderate level and is correlated with caregiver reactions. Rehabilitation professionals should actively guide caregivers, enhance their emotional regulation abilities, and reduce the SPB of patients.